2018
DOI: 10.7759/cureus.3303
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Stereotactic Spine Navigation for Posterior Partial Vertebrectomy in an En Bloc Resection of a Superior Pulmonary Sulcus Tumor Invading the Thoracic Vertebrae: A Technical Note

Abstract: Prior to the development of en bloc techniques, vertebral invasion by non-small cell lung cancer (NSCLC) had been considered a relative contraindication to surgical intervention. However, reports in the literature have demonstrated increased progression-free survival with the use of neoadjuvant chemotherapy followed by anterior en bloc resection of the residual tumor. Stereotactic spine navigation has been shown to improve accuracy during complex vertebral osteotomies, improving patient outcomes. We report a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…We recently started to use an intraoperative CT navigation system to increase surgical accuracy. The osteotomy trajectory can be monitored to prevent violating the tumor capsule 31 . It is particularly useful for intraosseous tumors, which have no soft-tissue extension, hence offering no visible limits to guide instrument placement.…”
Section: Discussionmentioning
confidence: 99%
“…We recently started to use an intraoperative CT navigation system to increase surgical accuracy. The osteotomy trajectory can be monitored to prevent violating the tumor capsule 31 . It is particularly useful for intraosseous tumors, which have no soft-tissue extension, hence offering no visible limits to guide instrument placement.…”
Section: Discussionmentioning
confidence: 99%
“…Benjamin et al 19 reported their use of 3D reconstructed diffusion tensor MRI integrated with a microscopeenabled navigation system to safely resect 2 intramedullary tumors by visualizing the orientation of spinal cord tracts and their relationship with the tumor in real time. Further work is needed to determine how accurate navigation can be for these microsurgical cases where motion artifact from cerebrospinal fluid pulsations and respiratory dynamics may introduce error into 47 Sacral tumor resection 15,52 Step-by-step confirmation of the tip of the osteotome Perform neural decompression in distorted anatomy Navigated dilator LLIF 11,18,23 Determine the site of the incision Advance through the psoas muscle while stimulating the nerves to prevent nerve injury Confirm appropriate retractor positioning over the disc space Target the next disc space if a multilevel LLIF is to be performed Confirm localization and trajectory Navigated chisel High sacral amputation in sacral chordoma 51 Help obtain maximal control during the procedure because of constant visual feedback on the depth of the cut Navigated probe OLIF 25 Pedicle subtraction osteotomy at the cervicalthoracic junction 5 En bloc resection of tumor 13,15,51,57,61 Localize the midportion of the pathological disc space from a true lateral trajectory on the skin Confirm correct disc space and trajectory Check the depth of the dissection to avoid disrupting the soft tissues of the anterior and lateral neck Verify the working angle as the osteotomy is being performed Verify the location of the endplates to avoid entering the adjacent disc spaces Verify the ideal depth of the osteotomy before closure Identify the trajectories needed for the osteotomes Identify and verify exact bony landmarks and tumor margins Navigated trial LLIF 11,18,23 Helps determine the size of the final cage selection OLIF 25 Navigated holder LLIF 11,18,23 Allows insertion of the cage with image guidance OLIF 25 Navigated high-speed drill Pedicle subtraction osteotomy 17 Perform vertebral body triangular resection of T12 hemivertebra via a posterior approach Tumor resection 36,55 Perform intraoperative resection of the nidus of osteoi...…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Найскладнішими пухлинами для застосування ендоскопічних утручань є пухлини тіл хребців з компресією спинного мозку [3]. Глибина рани, наявність легень, аорти, парної та напівнепарної вен, масивні кісткові структури суттево обмежують застосування ендоскопічних утручань [4]. Останнім часом є спроби використання ендоскопічних технік для видалення пухлин тіл хребців [5].…”
Section: результаты непосредственно после хирургического вмешательстunclassified